2016
DOI: 10.1177/0269881116662633
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic neurotransmission in emotional processing: New evidence from long-term recreational poly-drug ecstasy use

Abstract: The brain’s serotonergic system plays a crucial role in the processing of emotional stimuli, and several studies have shown that a reduced serotonergic neurotransmission is associated with an increase in amygdala activity during emotional face processing. Prolonged recreational use of ecstasy (3,4-methylene-dioxymethamphetamine [MDMA]) induces alterations in serotonergic neurotransmission that are comparable to those observed in a depleted state. In this functional magnetic resonance imaging (fMRI) study, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…However, MDMA has lower addiction potential than other stimulants such as cocaine or methamphetamine, and regular chronic use is rare (Solowij et al., 1992). If MDMA were only legally available in pharmacies, then pharmacists would be able to stress that infrequent moderate usage of MDMA poses significantly less risk (Laursen et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, MDMA has lower addiction potential than other stimulants such as cocaine or methamphetamine, and regular chronic use is rare (Solowij et al., 1992). If MDMA were only legally available in pharmacies, then pharmacists would be able to stress that infrequent moderate usage of MDMA poses significantly less risk (Laursen et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Kish et al (2010) described significant decreases in hippocampus (−20.8%, p < 0.01), frontal cortex (−27.3%, p < 0.01), occipital cortex (−46.1%, p < 0.01), temporal cortex (−26.7%, p < 0.01), parietal cortex (27.3%, p < 0.01), insular cortex (−26.3%, p < 0.01), and anterior cingulate cortex (−19.2%, p < 0.01). Laursen et al (2016) found significant results in the amygdala (−26.0%, p < 0.001). See Appendix 1 in Supporting Information S1 for a complete overview of data extracted regarding SERT availability.…”
Section: Sertmentioning
confidence: 84%
“…SERT availability was measured in different ways. Two studies (de Win et al, 2004;Reneman et al, 2001) McN5652 was used as a SERT radioligand in one study (Thomasius et al, 2006) and [ 11 C] DASB in the other three (Kish et al, 2010;Laursen et al, 2016;McCann et al, 2008).…”
Section: Sertmentioning
confidence: 99%
See 2 more Smart Citations